Penerapan Pembelajaran Taḥfiẓ Al-Qur'an Melalui Metode Takrir Dalam Meningkatkan Kualitas Hafalan Al-Qur'an Siswa - Irani, Anasya Salsavadya; Rahmawati, Sri Tuti (An-Nuha, 2024)
In recent years, many formal and informal Islamic school education, both Taḥfīẓ Al-Qur'an boarding schools and Taḥfīẓ houses, have included the Taḥfīẓ Al-Qur'an program into the school learning curriculum, because it is influenced by the trend of memorizing the Al-Qur'an which growing among the Muslim community in Indonesia. which is now spread in almost all parts of Indonesia. This study aims to determine the application of learning Taḥfiẓ juz 30 with the takrir method and instructor strategies in improving the quality of memorization of class VII students at MTsN 01 Lebak Rangkasbitung. This study used a qualitative approach with a descriptive research type. The location of the research was carried out at MTs Negeri 01 Lebak Rangkasbitung. The subjects of this study were the headmaster of the Madrasah, the school committee, the chief instructor of Taḥfīẓ, 5 instructors of Taḥfīẓ, 12 class VII students. Data collection techniques used in research are observation, interviews, and documentation. While the data analysis techniques used are data collection, data reduction, and data conclusion. The results of the study on the application of learning Taḥfiẓ AlQur'an at MTsN 01 Lebak Rangkasbitung showed an increase in the quality of memorizing the Al-Qur'an juz 30 based on assessments of Tajwid, Fashohah, and fluency of memorization by means of methods and strategies applied in learning by instructors Taḥfiẓ MTsN 01 Lebak Rangkasbitung.